The effect of artificial diet made of soybeans (Glycine max L.) on the rearing of Spodoptera frugiperda (Lepidoptera:Noctuidae) - Sulaeha Thamrin; Nurul Syafira Zuliana; Sylvia Sjam; Melina Melina (Universitas Lampung, 2022)
Spodoptera frugiperda is a novel invasive pest of maize crops. Therefore, studies on this pest are limited. Research on the use of artificial diets in S. frugiperda larvae rearing is essential to facilitate the provision of test larva stocks for lab-scale study purposes. The aim of this research was to figure out the effect of an artificial diet from soybeans as a protein source on S. frugiperda rearing. The parameters observed in this research were larval-stage longevity, larval survival rate, pupa size, sex ratio, pupal-stage longevity, pupal survival rate, fecundity, and nutritional index. The results showed that an artificial diet with soybeans had a significant effect on sex ratio, pupal survival rate, relative consumption rate (RCR) 4.89 g/g/day (4th instar); 1.99 g/g/day (5th instar), approximate digestibility (AD) 98.39% (4th instar); 95.45% (5th instar), and fecundity, but it did not have any significant effect on larval-stage longevity, larval survival rate, pupa size, pupal-stage longevity, the efficiency of conversion of ingested food (ECI) 3.68% (4th instar); 7.84% (5th instar), and efficiency of conversion of digested food (ECD) 3.76% (4th instar); 8.27% (5th instar). Artificial diet-based soybean was highly potential to be used in S. frugiperda rearing.